POLITIK HUKUM PEMBENTUKAN RANCANGAN UNDANG-UNDANG PENGHAPUSAN KEKERASAN SEKSUAL DI INDONESIA - Aryon Andria Adiyatma; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The Republic of Indonesia is a state of law. Where the rights of citizens are protected by the state. Sexual violence is a disease that is deeply rooted in the lives of Indonesian people. From year to year cases of sexual violence have increased. Regarding the existing regulations, it has not provided legal certainty for victims of sexual violence. The PKS Bill is a proposal to provide legal certainty for victims of sexual violence. The purpose of writing this thesis, namely: First, to find out the legal politics of the formation of the law on the elimination of sexual violence in Indonesia. Second, to find out the urgency of forming a draft law on the elimination of sexual violence in Indonesia.This type of research is normative research, where this research uses a research methodology on the legal principles that exist in the formation of legislation. The data sources used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials, the data collection technique in this study is the literature review method, after the data is collected then analyzed to draw conclusions.From the results of the research, it is concluded that, First, through a political perspective, law is seen as a product of politics. Sexual crimes are serious crimes in the handling of victims' rights tend not to be fulfilled, therefore in the formation of the Draft Law on PKS must pay attention to the rights of victims, including; right of treatment, protection and remedy. Second, the state must provide protection and security guarantees to the community as a constitutional right recognized by the state. Regulations related to sexual violence have not provided a clear legal umbrella so that a legal product is needed to provide legal certainty to the community.Keywords: Legal Politics - Sexual Violence - PKS Bill